Discoveries in the ruins of Nineveh and Babylon : with travels in Armenia, Kurdistan and the desert : being the result of a second expedition undertaken for the trustees of the British Museum - Layard, Austen Henry, 1817-1894. (London)
2 cilt (1. c. xxiii, 336 sayfa, 2 katlı resim, 1 katlı plan ; 2. c. sayfa [337]-686, 1 katlı plan, 2 katlı harita)